Evaluation of Renessans (Iodine Complex Molecule) Safety in Human Beings: An Open-Labeled Clinical Study. Issue 4 (3rd October 2022) - Kamal, Ahmad; Mahmood, Asif; Zaman, Muhammad; Farooq, Muhammad; Nasir, Bilal; Islam, Nasir; Sarfraz, Rai Muhammad; Zafar, Nadiah; Murtaza, Ghulam; Raheel, Abdul-Basit; Shahid, Areeba; Abid, Zahra; et al.
Extensive studies on evaluation of effectiveness/toxicity of different oral doses of iodine have not been explored yet. An open-labeled phase I clinical studies were conducted using iodine complex based research compound called Renessans. Study groups were observed for development of any adverse/serious adverse events and alteration in laboratory values of vital organs, TSH and T4 hormones before and after the administration of the products. Out of 31 consented individuals, 24 healthy individuals participated in the study. Rate of occurrence of mild Adverse Events (AEs) in group A was 8.3% while in Group B it was 33.33% but these Adverse Events were self-resolving. After completion of study treatment blood serum iodine was reported to 3522.88 µg/l while mean urine iodine concentration (MUIC) was greater than 2000 µg/l. Hormonal and vital organ's testing revealed that all parameters of TSH and T4, LFT, CBC, RFT remained unaltered except from ALT-SGPT ( P-value = .006) and AST-SGOT ( P-value = .02). From all of these findings, it can be inferred that the use of Renessans formulations did not pose any sort of risk to human body and can be considered safe through this pilot study. Graphical Abstract